The World Bank Contribution to Private Participation in Infrastructure - Karasapan, Omer (World Bank, Washington, DC, 2012)
The World Bank operations over the past seven years have included substantial activities in support of private participation in infrastructure (PPI). The author shows that, in keeping with its mandate, the Bank has focused primarily on policy-related PPI support, for example, to establish an appropriate legal and regulatory environment and on the least developed regions, especially Africa.